2020
DOI: 10.3389/fphys.2020.00789
|View full text |Cite
|
Sign up to set email alerts
|

Principles of the Mechanism for Epimuscular Myofascial Loads Leading to Non-uniform Strain Distributions Along Muscle Fiber Direction: Finite Element Modeling

Abstract: Pamuk et al. Mechanism for Non-uniform Muscle Fiber Strain effects get more pronounced with stiffer epimuscular connections. Assessments of forces exerted on the muscle by the epimuscular connections showed that such strain heterogeneities are ascribed to epimuscular myofascial loads determined by muscle relative position changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…The effects of myofascial force transmission on adjacent synergistic muscles have been further studied by the finite element modeling (Yucesoy et al, 2003a ; Pamuk et al, 2020 ). These studies suggest that the myofascial force transmission has major effects on skeletal muscle mechanics.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of myofascial force transmission on adjacent synergistic muscles have been further studied by the finite element modeling (Yucesoy et al, 2003a ; Pamuk et al, 2020 ). These studies suggest that the myofascial force transmission has major effects on skeletal muscle mechanics.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that muscle's extramuscular and epimuscular (i.e., collagen reinforced connective tissue structures including neurovascular tracts, general and compartmental fascia, intermuscular septa, interosseous membranes connecting muscle's epimysium to non-muscular structures and also other muscles, respectively), connections affect not only the global mechanics of the muscle i.e., the muscle force (Maas et al 2003;Yucesoy et al 2006), but also locally the myofascial loads Yucesoy 2010) can alter the mechanical equilibrium determining length changes along the muscle fascicles (Pamuk et al 2016;Karakuzu et al 2017). Principles of effects of such epimuscular myofascial force transmission (EMFT) leading to local muscle fiber direction length changes have been shown recently (Pamuk et al 2020). Consequently, compared to truly isolated muscle, we hypothesized that for such integrated muscle the effects of active state titin as the third myofilament on muscular mechanics are manipulated by EMFT.…”
Section: Introductionmentioning
confidence: 99%
“…position changes were shown to include strains opposing those determined by the globally imposed conditions(Pamuk et al 2020): (1) in passively lengthened integrated muscle, locally shortened regions and (2) in isometrically activated integrated muscle locally lengthened regions were shown.Note that, those model scenarios represent principles of previous experiments conducted in human muscle in vivo(Huijing et al 2011;Pamuk et al 2016) in which e.g., passively imposed proximal lengthening of the biarticular target muscle led to relative position differences with the monoarticular synergist. The distally directed myofascial loads arising from the stretching of the intermuscular connections, overcoming locally the globally imposed lengthening and yielding shortening in the distal ends of fascicles was the proposed explanation.…”
mentioning
confidence: 98%
“…More details on muscle function on the tissue scale can be obtained by employing three-dimensional, continuum-mechanical skeletal muscle models (based on the theory of finite elasticity), as it is possible to resolve the anatomical structure of tissues and spatial heterogeneities. Such continuum-mechanical models have, for example, been used to study intramuscular force transmission (Huijing, 1999 ; Yucesoy et al, 2003 ), the influence of the muscle fiber architecture and geometry on force output and tissue deformations (Huijing and Slawnych, 2000 ; Blemker and Delp, 2005 ; Fiorentino and Blemker, 2014 ; Seydewitz et al, 2019 ; Cankaya et al, 2021 ), the influence of motor unit activity and distribution (Röhrle et al, 2012 ; Schmid et al, 2019 ), or the interplay between different tissues/structures (Röhrle et al, 2017 ; Ramasamy et al, 2018 ; Pamuk et al, 2020 ). Further, employing the concept of classical field theories, continuum-mechanical muscle models offer great flexibility within multi-physics modeling frameworks and thus represent an important component to realize the vision of in silico laboratories (cf.…”
Section: Introductionmentioning
confidence: 99%